The concept of welfare state - Sankhdher, M. M. (Delhi : Publication Division, University of Delhi, 1975)
The objective of this study is to trace the genesis and development of the concept of the welfare state with a view to discover its theoretical foundations and to discern the elements that have gone into the making-up of the foundations.
Originally presented as the author's thesis, University of Delhi, 1973.
Includes bibliographical references and index.
rpm 18/10/2017
Loans
Keywords: Welfare state; Great Britain -- Social policy; Economic policy; Great Britain